Entre Tintín y Tartarín: la misión Dacar-Yibutí En el origen de la etnografía francesa - Brumana, Fernando Giobellina (Revista de Antropologia, 2002)
The Dakar-Djibuti Mission, under Marcel Griaule's guidance, crossed the African continent between 1931 and 1933. This esay describes the links between the expedition and French ethnography at the moment of its birth, as well as the way the latter one was organized and developped.